2016
DOI: 10.2196/cancer.5711
|View full text |Cite
|
Sign up to set email alerts
|

EHealth Acceptance and New Media Preferences for Therapy Assistance Among Breast Cancer Patients

Abstract: BackgroundElectronic health (eHealth) and mobile communication-based health care (mHealth) applications have been increasingly utilized in medicine over the last decade, and have facilitated improved adherence to therapy regimens in patients with chronic conditions. Due to the long duration of breast cancer therapy, and the long course of disease in metastatic breast cancer, a need for more intensified physician-patient communication has emerged. Various support mechanisms, including new media such as mHealth … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 23 publications
(23 reference statements)
5
29
0
Order By: Relevance
“…This result is similar to finding in other studies suggesting that Internet acceptance has reached an older age group, probably because patients older than 60 years are currently more familiar with the Internet than reported in previous studies ( Santana et al, 2011 ), and indicates that the use of the Internet for health-related questions appears to be feasible for most patients ( Drewes et al, 2016 ). In future years, with the increase of Internet access and computer literacy in society, we expect a growing interest in therapy assistance via digital health platforms.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This result is similar to finding in other studies suggesting that Internet acceptance has reached an older age group, probably because patients older than 60 years are currently more familiar with the Internet than reported in previous studies ( Santana et al, 2011 ), and indicates that the use of the Internet for health-related questions appears to be feasible for most patients ( Drewes et al, 2016 ). In future years, with the increase of Internet access and computer literacy in society, we expect a growing interest in therapy assistance via digital health platforms.…”
Section: Discussionsupporting
confidence: 90%
“…The Internet has become an accessible source for individuals to research information, including for their medical issues, and patients with cancer are among the most frequent such users ( Drewes et al, 2016 ). This reflects the development of Internet educational programs available for breast cancer patients that, at the moment, are focused mostly on increasing patients’ knowledge through information related to both the disease and the procedures ( Warren et al, 2014 ).…”
Section: The Opportunities Of Ehealth Interventionsmentioning
confidence: 99%
“…In general, cancer patients positively value the use of Internet-based technologies for health care management and feel comfortable using them [ 22 ]. Breast cancer patients usually use this technology to seek general information, search for therapies or scientific data, and exchange information with other patients [ 23 ]. Authors have also pointed out the importance of including customizable functionalities in mobile phone apps in order to manage care-related information so that these features can be easily modified depending on changes in the user’s needs [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, cancer survivors were positive toward ePOAs that enable them to enhance their own QoL and support them in finding tailored supportive care [ 57 ]. It was shown that eHealth applications are well accepted for therapy assistance in general (like patient-physician communication) and eHealth programs as a part of usual health care may be promising [ 29 , 50 , 57 ]. A promising result of our study is that a substantial group of participants in need of supportive care prefer ePOAs for the delivery of adequate psychosocial care.…”
Section: Discussionmentioning
confidence: 99%
“…Cancer patients represent a growing proportion of health information seekers [ 30 , 35 ]. Over the last decade, a growing body of studies regarding the application of eHealth [ 29 , 36 , 37 ] and different online interventions [ 38 ] have been published and are widely used in psycho-oncological care [ 39 ]. While online searches for cancer information, eHealth applications, and online interventions in psycho-oncological care are more common, less is known about cancer patients’ real demands for online and offline psycho-oncological interventions [ 38 , 40 ].…”
Section: Introductionmentioning
confidence: 99%